2014
DOI: 10.1007/s00404-014-3398-y
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene citrate ‘stair-step’ protocol vs. traditional protocol in patients with polycystic ovary syndrome: a randomized controlled trial

Abstract: The stair-step protocol was determined to have a significantly shorter treatment period without any detrimental effect on the ovulation and pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
2
17
4
Order By: Relevance
“…Similarly, Deveci et al . [ 5 ] after performing similar study reported his results with an ovulation rate of 43.3% in the study group and 33.3% in the control group.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, Deveci et al . [ 5 ] after performing similar study reported his results with an ovulation rate of 43.3% in the study group and 33.3% in the control group.…”
Section: Discussionsupporting
confidence: 52%
“…Deveci et al similarly found no difference in endometrial thickness between these two treatment protocols in their study of women using up to two cycles of CC. 21 Our study differs from that of Deveci et al 21 in that we randomly assigned patients before their first dose of CC. In contrast, the retrospective study by Budinetz et al showed that endometrial thickness was significantly less in the stair-step cycle than in the subsequent CC cycle, in which the dose of CC was increased if no response was seen by day 14, 20 much earlier than the reassignment day in our study (day 21).…”
Section: Cycle 1 (N = 14)mentioning
confidence: 77%
“…19 Furthermore, the time to ovulation was 23 to 35 days with the stair-step protocol compared with 55 to 88 days with the traditional protocol. 19 Only one study has had sufficient statistical power to detect a difference between pregnancy rates in women undergoing a stair-step protocol and women undergoing a traditional protocol after a maximum of two cycles of CC with a maximum daily dose of 100 mg. 21 In that study, the pregnancy rates between groups were similar: 16.7% in the stair-step approach and 10% in the traditional protocol, but the duration of treatment was 28.1 days shorter in the stair-step approach. 21 Although our study appeared to show a faster time to ovulation (15 days) in women using the stair-step protocol compared with a traditional protocol, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations